INTEGRATION AND ASSIMILATION AS THE IMPACTS OF DIASPORA EXPERIENCE REFLECTED IN THE WANG FAMILY IN THE FAREWELL (2019) MOVIE - Rahmadila Wulandari; Afina Murtiningrum (Universitas Duta Bangsa Surakarta, 2025)
This study analyzes The Farewell movie by focusing on the impacts of diaspora experience perceived by the Wang family using Berry's theory. Data of this study is obtained through dialogue and monologue from the movie script. This study is qualitative research through the process of collecting data qualitatively and reporting it descriptively. This study shows how diaspora issues related to integration and assimilation as the impacts of diaspora experience are reflected in The Farewell movie. The results of this study show that the first-generation diaspora experienced cultural integration while the second-generation diaspora experienced cultural assimilation.